Smartfon w klasie: Od zabawki do narzędzia edukacyjnego - Brosch, Anna (Studia Edukacyjne, 2018)
Today’s children are growing up in a digital age that is far different from that of previous generations. Young children’s use of interactive screen media such as smartphones is increasing rapidly. A variety of mobile devices are all around, but they are still not accessible enough at schools, where the use of smartphones is usually forbidden.The aim of this research was to discover teachers’ opinion about using smartphones in class. The qualitative methodology was used in this study to analyse in depth the contextual factors concerning the use of smartphones during the education process. The analysis was based on data from 32 interviews with primary school teachers. The results of the study have shown that teachers do not incorporate smartphones into the education process, despite their positive attitude towards this kind of mobile devices.